Relationship of Characters and Illustration in Short Story 9 Dari Nadira By Leila S. Chudori - Sri Ayu Kusumaningsih; Ahmad Bahtiar (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study is to find out the relationship of characters to illustrations in a collection of 9short stories from NadiraKarya Leila S. Chudori. In the collection, there are four short stories that contain illustrations of the main characters namely "Melukis Langit”, "Tasbih", "Sebilah Pisau", and "At Pedder Bay". The method used in this research is descriptive qualitative method by using Charles Sanders Pierce's Semiotic Theory which includes sign and object. The study of characterization or characterization is done in two methods namely direct (telling) and indirect (showing). The results of  this study indicate that out of the 4 short stories analyzed only 3 short stories that have character relationships with illustrations, namely the short story "Melukis Langit", "Tasbih" and "Sebilah Pisau". Short story of "Melukis Langit" depicts Nadira's character who is strong against her father's behavior since the death of his mother. The short story illustration shows Nadira crying in the bathroom to vent her sadness. Short story "Tasbih" describes Mr. X with a mysterious character illustrated by showing Mr. X's face full of mystery while the short story "Sebilah Pisau" tells Kris who is Nadira's secret admirer. Kris's character is displayed with illustrations illustrating the event when Nadira was surprised to see Kris's table filled with Nadira's picture. Short story "At Pedder Bay" tells Nadira's old friend Marc who is also an admirer of Nadira for a long time. The main character, Marc in this short story is not illustrated in the illustration. The short story shows a background, namely the lake and the figure of the woman sitting pensively.